HUBUNGAN INTAKE MAKANAN (KALORI) DENGAN KELELAHAN KERJA PADA PERAWAT SHIFT PAGI UGD PAVILIUN RS. X JAKARTA - Cahyanti, Dwi; Suwondo, Ari; Widjasena, Baju (Jurnal Kesehatan Masyarakat (Undip), 2015)
Results of studies in several countries show that work fatigue contributed significantly to workplace accidents. Nurses as the spearhead of hospital health care, if they experience fatigue then the bad effects of fatigue can not only be detrimental to nurse itself but can also affect the patient. One of the major contributing factors to the occurrence of fatigue is food intake (calories). This study aim to determine the correlations of food intake (calories) with work fatigue in morning shift nurses of ER Pavilion Hospital X Jakarta. This type of research was descriptive analytic with quantitative research methods and used cross sectional study design. The independent variable was food intake and the dependent variable was work fatigue. Confounding variables studied consisting of gender, age, work period and work motivation. The sample used to this study is total population throughout morning shift nurses of ER Pavilion Hospital X Jakarta, amounting to 32 people with a sample of respondents who are willing to be as many as 30 people. Analysis of data used univariate and bivariate analysis with Chi Square test (significance level 0.05). Results of univariate analysis showed that nurses with less intake is 63.3% and nurses with the work fatigue is 73.3%. Bivariate analysis results indicated that there was no correlation of food intake (calories) with fatigue based alternative test Fisher's Exact Test (ρ=0104) but there is a correlation between food intake with work fatigue who had ≥ 2 years working period (ρ=0.035). Researchers suggest to nurses to suffice the needs of calories, especially the nurses who worked ≥2 years to prevent fatigue.